2015
DOI: 10.3340/jkns.2015.57.6.478
|View full text |Cite
|
Sign up to set email alerts
|

Two Case Reports and an Updated Review of Spinal Intraosseous Schwannoma

Abstract: We report two rare cases of spinal intraosseous schwannoma (SIS) with sustained myelopathy symptoms and provide an updated review regarding SIS in the literature. A 71-year-old man experienced right lumbocrural pain and gait disturbance accompanied with paresthesia and right leg weakness. Imaging examinations revealed a mass with lesions in L4 vertebral body causing bone destruction and spinal cord compression. Complete resection of the well-demarcated tumor and posterior fusion were performed. A 54-year-old f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
1
8
0
2
Order By: Relevance
“…Tumors originating from neural tissue in the spinal canal may rarely cause bony scalloping, but it is very rare to cause vertebral body destruction 2 . There are few case reports of schwannomas causing extensive vertebral body erosion 3, 4. We report a case of spinal cord astrocytoma with extensive erosion of the vertebral body.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Tumors originating from neural tissue in the spinal canal may rarely cause bony scalloping, but it is very rare to cause vertebral body destruction 2 . There are few case reports of schwannomas causing extensive vertebral body erosion 3, 4. We report a case of spinal cord astrocytoma with extensive erosion of the vertebral body.…”
Section: Discussionmentioning
confidence: 93%
“…Tumors originating from neural tissue in the spinal canal may rarely cause bony scalloping 2 . There are also few case reports of schwannomas with associated vertebral body destruction 3, 4. Otherwise, it is very rare for tumors originating from the spinal canal neural tissues to cause significant bony changes.…”
Section: Introductionmentioning
confidence: 99%
“…O schwannoma é um tumor de bainha nervosa, sendo, portanto, intradural extramedular, embora alguns possam crescer a ponto de terem componente extradural ou mesmo serem completamente extradurais, 1,4 havendo inclusive relato de casos em que o schwannoma não se liga ao tecido nervoso. 5 Em geral, o schwannoma de cauda equina clássico apresenta crescimento lento, o que torna seus sintomas tardios. Quando sintomático, esse tumor causa, na maioria dos casos, dor, a qual piora durante a noite, e alterações na sensibilidade, uma vez que a neoplasia normalmente se estabelece em raízes sensitivas.…”
Section: Discussionunclassified
“…embora raros casos de extensa erosão óssea por neoplasia nessa localização já tenham sido descritos. 5 Esse tumor também pode ter uma apresentação plexiforme com uma forma multinodular, embora essa variante seja mais comum em região de cabeça e pescoço, sendo extremamente rara na região da cauda equina tendo apenas um caso sido relatado na literatura de schwannoma plexiforme em cauda equina. 9 Clinicamente, é possível que a mielopatia ou radiculopatia, como no caso relatado, decorrente de uma compressão nervosa causada por schwannoma, seja confundida com herniação de disco, tumor ou mesmo, mais raramente, doenças desmielinizantes.…”
Section: Discussionunclassified
“…Reported locations include the mandible, maxilla, spine, petrous apex and, uncommonly, the long bones of the extremities. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Of 165 IOS cases reviewed by Suzuki et al, 18 only 10 cases (6%) were found in the sacrum.…”
Section: Introductionmentioning
confidence: 99%